Analysis of the pectin extraction process at recycling of secondary material resources - Chabanova, Oksana; Bondar, Sergii; Kotliar, Yevhenii; Nedobiychuk, Tatiana; Verkhivker, Yakiv (Technology audit and production reserves, 2021)
The object of research is the secondary material resources of processing plant and animal raw materials, namely fruit pomace and milk whey. One of the most problematic areas is that the waste of these industries has high rates of biological and chemical oxygen consumption of wastewater, which significantly impairs the operation of local and city treatment facilities. In addition, the parameters of extraction and determination of the quality indicators of the obtained product are not well defined. The processing of whey and pomace of fruit crops can reduce the environmental burden on the environment and increase the efficiency of technological processes through resource conservation and obtaining a surplus product. The problem is solved, in particular, by using the process of extracting plant waste using milk whey and the process of energy-saving membrane concentration. In the course of the study, let’s use pectin-containing plant waste from juice production, namely watermelon, pumpkin, quince, beetroot, apple and a mixture of orange and tangerine pomace. The results obtained indicate that the process of extracting apple pomace with milk whey is promising, since the highest pectin content in the extract is established for apple pomace. The main amount of pectin substances passes into the extract starting from 75 minutes to 90 minutes. Extraction-hydrolysis for 2 hours at a temperature of 85 °C, pH=2–2.5 units determines the best results. Ultrafiltration of the obtained extract makes it possible to increase the pectin content up to 3.0 % with a protein content of more than 6.0 %. The membranes used in the experiment are characterized by high selectivity for protein and pectin. The fact is established that diafiltration makes it possible to effectively purify whey-pectin concentrates from ballast impurities with simultaneous enrichment of the concentrate with high-molecular components of whey. A technological scheme for the production of pectin-whey concentrate with high organoleptic and detoxification characteristics is proposed. The proposed technological process has a number of positive features, in particular, a high content of pectin substances, high value indicators, a significant reduction in the burden on the environment, economic benefits through energy conservation and obtaining a surplus product.